Análise dos atributos quali-quantitativos da água em microbacia perene do semiárido brasileiro - Oliveira Júnior, Raimundo Fernandes de (Universidade Federal Rural do Semi-Árido, 2020)
The monitoring of water quality attributes of springs and their water courses in hydrographic basins is essential to understand the dynamics between land use and occupation and water demand for multiple uses. Therefore, analyzing and diagnosing the spatial-temporal variability of these attributes is an important step in the prognosis of water resources and a basis for decision-making in their integrated management. Multivariate statistics has increasingly contributed to the research of qualitative attributes of water in watersheds. Therefore, this research aimed to evaluate the influence of anthropic action on the quality and quantity of water in the spring and perennial stream of a watershed in the Brazilian semiarid, using multivariate statistics to select the most important physical-chemical characteristics in the quality variability. from water. The study watershed belongs to the middle course of the hydrographic basin of the ApodiMossoró River, located in the west of the state of Rio Grande do Norte. Space-time monitoring of water quality was carried out in the Riacho da Bica watershed in the period from 2016 to 2018, making 15 collection campaigns for the diagnosis of water quality attributes. It was possible to observe that along the stream of the spout, there were anthropic and natural influences on the quality and quantity of the water. The water in the Riacho da Bica watershed was classified for irrigation purposes as medium risk of salinity and sodicity in the rainy season, in the dry season it was low risk of salinity and high risk of sodicity. The application of multivariate statistics, generated through the analysis of main and factorial components, four main components through which it was possible to identify the main attributes that explain the variability of water quality in the watershed
Keywords: Qualidade de água; Estatística multivariada; Nascente; Uso do solo; Recursos hídricos; Water quality; Multivariate statistics; Spring; Land use.; Water resources; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO